حماية الموارد البيئية في التشريع الجزائري - وليد جوامع; إشراف لوكام (My University, 2023)
SOUMARY The subject of the memorandum is "Protection of environmental resources in Algerian legislation", to determine the effectiveness of legal and institutional cooperation at the central and local level, as well as the role of the civil society concerned with the environment in Algeria in this protection, in accordance with international environmental treaties and conventions, as well as other legislation. And in light of the above and understanding the purpose of this study, we will divide the topic into two chapters, we will dedicate the first chapter to the main environmental resources in Algeria, namely the water and air environment, as well as soil resources, as well as the most important environmental damage that affects these precious components, but And it is environmental pollution and its impact on it, except that the Algerian legislator did not stop at these encroachments on these resources in the same way as other legislation, where he acted on the empowerment of various bodies, whether at the central or local level, with legal intimidation by means of various executive mechanisms, which were detailed in the second chapter, starting from Preventive measures, which turn into rejection in the case of visible damage to these resources, are embodied in the imposition of penalties on everyone who harms them, which vary according to the damage caused, and this enables them to actively protect these resources in addition to their constitutional protection, in addition to the participation of civil society activists who play a special role for maintaining it from all forms of danger. ..................... ملخص يأتي موضوع المذكرة الموسوم "حماية الموارد البيئية في التشريع الجزائري"، لتحديد مدى فعالية الترسانة القانونية والمؤسساتية على المستوى المركزي والمحلي وكذا فواعل المجتمع المدني المعنية بالمجال البيئي في الجزائر في هذه الحماية ، تأثرا بالمعاهدات والاتفاقيات الدولية البيئية على غرار التشريعات الأخرى. وعلى ضوء ما سبق و بلوغا للهدف المرجو من هذه الدراسة ، فإننا نقسم الموضوع إلى فصلين ، خصصنا الفصل الأول لأهم الموارد البيئة في الجزائر، وهي البيئة المائية ، الهوائية بالإضافة مورد التربة ، كما تعرضنا فيه إلى أهم ضرر بيئي يصيب هذه المكونات الثمينة ، ألا وهو التلوث البيئي وتأثيره البليغ عليها ، إلا أن المشرع الجزائري لم يقف عند هذه التجاوزات على هذه الموارد على غرار التشريعات الأخرى ، حيث عمل على تمكين الهيئات المختلفة سواء على المستوى المركزي أو المحلي بترسانة قانونية بواسطة آليات إجرائية مختلفة تم تفصيلها في الفصل الثاني ، ابتداء من الإجراءات الوقائية التي تتحول الى ردعية في حالة المساس الظاهر لهذه الموارد ، تتجسد في تسليط عقوبات على كل من مسها بضرر والتي تختلف حسب الضرر المتسبب فيه، وهذا لتمكينها من حمايتها بشكل فعال فضلا عن الحماية الدستورية لها ، إضافة الى مشاركة فواعل المجتمع المدني التي تلعب دورا خاصا للمحافظة عليها من كل أشكال أنواع الخطر المحدق بها . ................................ RÉSUMÉ Le sujet du mémoire est "La protection des ressources environnementales dans la législation algérienne", afin de déterminer l'efficacité de la coopération juridique et institutionnelle au niveau central et local, ainsi que le rôle de la société civile concernée par l'environnement en Algérie dans cette protection, conformément aux traités et conventions internationaux sur l'environnement, ainsi qu'à d'autres législations. Et à la lumière de ce qui précède et en comprenant l'objectif de cette étude, nous allons diviser le sujet en deux chapitres, nous allons consacrer le premier chapitre aux principales ressources environnementales en Algérie, à savoir l'environnement de l'eau et de l'air, ainsi que les ressources du sol, ainsi que les dommages environnementaux les plus importants qui affectent ces composants précieux, mais Et c'est la pollution environnementale et son impact sur elle, sauf que le législateur algérien ne s'est pas arrêté à ces empiètements sur ces ressources de la même manière que d'autres législations, où il a agi sur l'habilitation de divers organes, Les mesures préventives, qui se transforment en rejet en cas d'atteinte visible à ces ressources, se concrétisent par l'imposition de sanctions à tous ceux qui leur portent atteinte, sanctions qui varient en fonction des dommages causés, ce qui leur permet de protéger activement ces ressources en plus de leur protection constitutionnelle, en plus de la participation des activistes de la société civile qui jouent un rôle particulier pour les préserver de toute forme de danger.